Mutant huntingtin-impaired degradation of beta-catenin causes neurotoxicity in Huntington's disease. - Godin, J.D.; Poizat, G.; Hickey, M.A.; Maschat, F.; Humbert, S. (The EMBO Journal, 2010)
Huntington's disease (HD) is a fatal neurodegenerative disorder causing selective neuronal death in the brain. Dysfunction of the ubiquitin-proteasome system may contribute to the disease; however, the exact mechanisms are still unknown. We report here a new pathological mechanism by which mutant huntingtin specifically interferes with the degradation of beta-catenin. Huntingtin associates with the beta-catenin destruction complex that ensures its equilibrated degradation. The binding of beta-catenin to the destruction complex is altered in HD, leading to the toxic stabilization of beta-catenin. As a consequence, the beta-transducin repeat-containing protein (beta-TrCP) rescues polyglutamine (polyQ)-huntingtin-induced toxicity in striatal neurons and in a Drosophila model of HD, through the specific degradation of beta-catenin. Finally, the non-steroidal anti-inflammatory drug indomethacin that decreases beta-catenin levels has a neuroprotective effect in a neuronal model of HD and in Drosophila and increases the lifespan of HD flies. We thus suggest that restoring beta-catenin homeostasis in HD is of therapeutic interest.